A Survey of Occupational Therapy Curricula. - Marshall, Edwinna (American Journal of Occupational Therapy, 1991)
Cross-sectional surveys were conducted of occupational therapy professional and technical programs. Part 1 describes general studies and prerequisite requirements for an entry-level baccaluareate degree in occupational therapy. Part 2 presents general studies, prerequisites, and technical curriculum of the occupational therapy assistant programs. Program directors design and manage professional programs based on their knowledge of academia, higher education, accreditation essentials, and consumer needs. Descriptive data of educational prerequisites and curriculum content are used in program evaluation and planning for accreditation, institutional strategic planning, marketing, projection of future needs, and facilitation of communication between curricula.